Physical education teachers' perspectives on the need for volleyball learning assessment application development - Destriani, Destriani; Destriana, Destriana; Victorian, Ahmad Richard; Rasyad, Irfan; Kencana, Ade Surya (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Research Problems: The absence of a suitable volleyball learning assessment application hinders physical education teachers from conducting effective evaluations, highlighting the need to explore their perspectives on developing such an application. Research Objectives: This study aims to determine the perspective of Physical Education teachers on the need to develop a volleyball learning assessment application. Through this study, various problems faced by teachers in the assessment process were identified and how the application can be an effective solution. Methods: The research method uses a qualitative questionnaire distributed via Google Forms to physical education, sports, and health teachers. The sample obtained was 123 Physical Education teachers. Data analysis in this study used descriptive statistics in the form of a frequency table. Results: Based on the results of the study, it was obtained that with the results 6.3 % strongly agree, 15% agree, 14% neutral, and 5% disagree, 3% strongly disagree. Conclusion: The study concludes that in general Physical education teachers have a positive view of the need to develop a volleyball learning assessment application, that assessment with the application will provide several advantages, such as making it easier to record and manage grades, increasing the accuracy of assessment data, and saving time in assessment. As a recommendation, so that in the future it can be used to support progress and ease in conducting assessments in volleyball material.